The Influence Of Self Reward And Self Healing On The Consumption Behavior Of Career Women In Parepare City With Religiosity As A Moderating Variable - Muh Yusuf Munir; Arwin; Muzdalifah Muhammadun; A. Rio Makkulau Wahyu; Umaima; Dian Resky Pangestu (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study was motivated by the increasing complexity of career women's consumption behavior. This behavior is influenced not only by basic needs, but also by psychological factors such as self-reward and self-healing. Religiosity is seen as a moderating variable that can control consumption behavior, especially in the context of a religious society in Parepare City. The purpose of this study is to analyze the influence of self-reward and self-healing on the consumption behavior of career women in Parepare City with religiosity as a moderating variable. The method used is a quantitative approach with a survey design. The sample was obtained through purposive sampling of 100 career women aged 18–50 years in Parepare City. The research instrument was a Likert questionnaire, while data analysis was performed using SmartPLS through validity and reliability tests, T-tests, determination coefficients, and path analysis. The results showed that self-reward and self-healing had a significant positive effect on consumption behavior. Religiosity also had a significant effect and was proven to moderate the influence of these two psychological factors. These findings contribute to consumer behavior science and provide practical benefits for career women in managing balanced consumption.